HYGIENE AND SANITATION OF SCHOOL CANTEEN (COMPARATIVE STUDY OF 9 PUBLIC JUNIOR HIGH SCHOOLS IN KEBAYORAN LAMA DISTRICT, JAKARTA SELATAN CITY) YEAR 2023 - Ernyasih; Dian Anggraeni; Nurmalia Lusida; Andriyani (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
The quality and cleanliness of food greatly affect the health of the humans who consume it, so one of the places for buying selling, and processing food that can affect the health of many people is the school canteen. School canteens must meet hygiene and health requirements to create a healthy canteen environment. The purpose of this study was to describe the Hygiene and Sanitation of Public Junior High School Canteens in Kebayoran Lama District. The method in this research is descriptive using a qualitative approach. Collecting data in this study by observation and interviews with data collection tools using interview guidelines, observation sheets (checklists), and documentation tools. The results of this study were the cleanliness of food handlers, the location and building of the canteen, the garbage disposal, and the washing hands of 9 canteens did not meet the requirements (100%), the clean water of 8 canteens met the requirements (89%), SPAL 5 canteens met the requirements (56%) and 2 places for washing equipment meets the requirements (22%). This study concludes that most school canteens do not meet hygiene and sanitation requirements according to the Minister of Health of the Republic of Indonesia No 1096 of 2011, so efforts to improve, supervise, and train-related parties are needed.